2017
DOI: 10.1103/physrevb.95.115407
|View full text |Cite
|
Sign up to set email alerts
|

High thermoelectric power factor in two-dimensional crystals ofMoS2

Abstract: The quest for high-efficiency heat-to-electricity conversion has been one of the major driving forces towards renewable energy production for the future. Efficient thermoelectric devices require high voltage generation from a temperature gradient and a large electrical conductivity, while maintaining a low thermal conductivity. For a given thermal conductivity and temperature, the thermoelectric powerfactor is determined by the electronic structure of the material. Low dimensionality (1D and 2D) opens new rout… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
154
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(174 citation statements)
references
References 56 publications
16
154
3
1
Order By: Relevance
“…With reducing thickness, the thermoelectric power factor (PF) keeps increasing until a peak, where a high ≈50 µW cm −1 K − 2 PF was shown for two‐layer MoS 2 sample in its ON state, before dropping greatly for the monolayer, which was theoretically attributed to a difference in the energy dependence of the electron MFP. A similar thickness‐dependent PF trend was reported in paper, where a relatively higher PF of two‐layer MoS 2 was demonstrated due to the better conductivity in the degenerate metallic regime and a large Seebeck coefficient due to the high valley degeneracies and large effective masses. Quite recently, Wu et al showed that the PF of layered MoS 2 can be even enhanced by a strong interaction of electrons at the Fermi level with a local magnetic impurity (i.e., sulfur vacancy) and this so‐called magnetic impurity‐induced Kondo effect leads to a new record PF around 50 mW m −1 K −2 , as shown in Figure d.…”
Section: Phonon‐driven Emerging Applications Of 2d Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…With reducing thickness, the thermoelectric power factor (PF) keeps increasing until a peak, where a high ≈50 µW cm −1 K − 2 PF was shown for two‐layer MoS 2 sample in its ON state, before dropping greatly for the monolayer, which was theoretically attributed to a difference in the energy dependence of the electron MFP. A similar thickness‐dependent PF trend was reported in paper, where a relatively higher PF of two‐layer MoS 2 was demonstrated due to the better conductivity in the degenerate metallic regime and a large Seebeck coefficient due to the high valley degeneracies and large effective masses. Quite recently, Wu et al showed that the PF of layered MoS 2 can be even enhanced by a strong interaction of electrons at the Fermi level with a local magnetic impurity (i.e., sulfur vacancy) and this so‐called magnetic impurity‐induced Kondo effect leads to a new record PF around 50 mW m −1 K −2 , as shown in Figure d.…”
Section: Phonon‐driven Emerging Applications Of 2d Semiconductorsmentioning
confidence: 99%
“…The bilayer MoS 2 shows a maximum PF with a larger electrical mobility. Reproduced with permission . Copyright 2017, American Physical Society.…”
Section: Phonon‐driven Emerging Applications Of 2d Semiconductorsmentioning
confidence: 99%
“…More recently, thickness‐dependent thermoelectric measurements were performed with cleaved MoS 2 flakes . Interestingly, the largest power factor of 8500 µW m −1 K −2 was realized in bilayer samples and is also the largest value among semiconducting thermoelectric materials (Figure f) . This large enhancement of the power factor in bilayer MoS 2 was not only because of 2D confinement effects but was also attributed to the large effective mass and valley degeneracies in the heavily doped conduction band.…”
Section: Thermoelectric Properties Of Single‐crystalline and Polycrysmentioning
confidence: 95%
“…More recently, thickness‐dependent thermoelectric measurements were performed with cleaved MoS 2 flakes . Interestingly, the largest power factor of 8500 µW m −1 K −2 was realized in bilayer samples and is also the largest value among semiconducting thermoelectric materials (Figure f) .…”
Section: Thermoelectric Properties Of Single‐crystalline and Polycrysmentioning
confidence: 96%
See 1 more Smart Citation